1H NMR studies of water- and alkaline-soluble organic matter from fine urban atmospheric aerosols. (October 2015) - Lopes, Sónia P.; Matos, João T.V.; Silva, Artur M.S.; Duarte, Armando C.; Duarte, Regina M.B.O.
Abstract: Solution-state 1 H NMR spectroscopy was applied to characterize the structural features of water- and alkaline-soluble organic matter (WSOM and ASOM, respectively) sequentially extracted from fine urban atmospheric aerosols collected over different seasons. The objectives of this study were twofold: (i) to compare the functional characteristics of fine aerosol WSOM and the yet unknown ASOM, and (ii) to assess the sources of WSOM and ASOM at an urban location. The 1 H NMR analysis confirmed that the WSOM and ASOM fractions hold similar 1 H functional groups; however, they differ in terms of their relative distribution throughout the seasons. The winter and autumn samples have a less aliphatic and oxidized character and higher contributions from aromatic groups than those of warmer conditions. The urban aerosol WSOM and ASOM fractions do not fit the established 1 H NMR source apportionment fingerprints of marine, secondary, and biomass burning organic aerosols (OAs), exhibiting a smaller relative contribution of carbon-oxygen double bonds, which is indicative of a less oxidized character. These results confirm that the boundaries of the pre-established source categories, especially for secondary and biomass burning OAs, might be different at urban locations, suggesting the need to improve the 1 H NMR source apportionment model for including a new fingerprint for urban OAs. Graphical abstract: Highlights: 1 H NMR spectroscopy was used to study urban organic aerosols in PM2.5 . Water and alkaline soluble components of urban organic aerosols have been compared. 1 H NMR spectral features and their seasonal variability have been investigated. Urban OA does not fit marine, secondary and biomass burning source fingerprints. Local anthropogenic origin of WSOM and ASOM have been suggested.